2017
DOI: 10.1007/s00277-017-2983-0
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood cytogenetics allows treatment monitoring and early identification of treatment failure to lenalidomide in MDS patients: results of the LE-MON-5 trial

Abstract: EudraCT:2008-001866-10.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Overall, we found that discrepancies in CNV detection can be accounted to more sensitive detection of abnormalities in CBA due to a proliferative advantage of the abnormal clone and due to smaller clone sizes in PB compared to BM supported by mutational analysis. In cases with large differences in clone size between BM and PB CD34-enriched PB samples might help to overcome these limitations [ 6 8 ].
Fig.
…”
Section: To the Editormentioning
confidence: 99%
“…Overall, we found that discrepancies in CNV detection can be accounted to more sensitive detection of abnormalities in CBA due to a proliferative advantage of the abnormal clone and due to smaller clone sizes in PB compared to BM supported by mutational analysis. In cases with large differences in clone size between BM and PB CD34-enriched PB samples might help to overcome these limitations [ 6 8 ].
Fig.
…”
Section: To the Editormentioning
confidence: 99%